2019
DOI: 10.1186/s12986-019-0418-8
|View full text |Cite
|
Sign up to set email alerts
|

CoQ10 enhances PGC1α and increases expression of mitochondrial antioxidant proteins in chronically ischemic swine myocardium

Abstract: BackgroundExpression of mitochondrial proteins is reduced within hibernating myocardium (HM). It is unclear whether dietary supplementation with CoQ10 can increase expression of mitochondrial electron transport chain (ETC) and antioxidant proteins within this tissue. In a swine model of HM, we tested whether dietary administration of CoQ10 for four weeks enhances the expression of ETC and antioxidant proteins within the mitochondria via increased PGC1α signaling.Methods12 swine were instrumented with a fixed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In human neuroblastoma (SH-SY5Y) cells pre-treated with water-soluble CoQ 10 following H 2 O 2 treatment, a significant reduction in mitochondrial ROS generation, preserved ΔΨm, increased mitochondrial ATP production, and the prevention of mitochondrial membrane collapse were observed in comparison with the control mitochondria. This suggests that CoQ 10 can act as a potent antioxidant at the mitochondrial level, as CoQ 10 has been demonstrated to stabilise the mitochondrial membrane and increase mitochondrial numbers as a consequence of H 2 O 2 -induced OS, which may be due to the ability of CoQ 10 to increase PGC1α signalling [ 142 , 145 , 146 ]. Studies with senescence-accelerated mouse (SAM) models have revealed that a diet supplemented with CoQ 10 can induce pathways involving SIRT1, SIRT3, and PGC1α, preventing mitochondrial deterioration by increasing OS resistance [ 143 ].…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…In human neuroblastoma (SH-SY5Y) cells pre-treated with water-soluble CoQ 10 following H 2 O 2 treatment, a significant reduction in mitochondrial ROS generation, preserved ΔΨm, increased mitochondrial ATP production, and the prevention of mitochondrial membrane collapse were observed in comparison with the control mitochondria. This suggests that CoQ 10 can act as a potent antioxidant at the mitochondrial level, as CoQ 10 has been demonstrated to stabilise the mitochondrial membrane and increase mitochondrial numbers as a consequence of H 2 O 2 -induced OS, which may be due to the ability of CoQ 10 to increase PGC1α signalling [ 142 , 145 , 146 ]. Studies with senescence-accelerated mouse (SAM) models have revealed that a diet supplemented with CoQ 10 can induce pathways involving SIRT1, SIRT3, and PGC1α, preventing mitochondrial deterioration by increasing OS resistance [ 143 ].…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…In a previous study, we observed no improvement in systolic functional recovery following adjunctive therapies such as CoQ10 [ 35 ]. When using an adjunctive MSC patch, however, we saw an improvement in systolic function without a significant increase in regional blood flow.…”
Section: Discussionmentioning
confidence: 81%
“…Additionally, an increased efficiency of mitochondrial respiration (adenosine diphosphate/oxygen ratio) was observed ( p < 0.12) [ 12 ]. This improvement in mitochondrial efficiency has also been demonstrated in a swine model of chronic myocardial ischemia, wherein CoQ10 supplementation (400 mg/day) for 4 weeks enhanced nuclear-bound PGC1-α, indicating the activation of mitochondrial biogenesis, and increased the expression of antioxidant proteins within the mitochondria [ 60 ].…”
Section: Coq10 and Heart Failure (Hf)mentioning
confidence: 78%